Forest-Smart Mining : Identifying Good and Bad Practices and Policy Responses for Artisanal and Small-Scale Mining in Forest Landscapes - World Bank Group (World Bank, Washington, DC, 2019)
Minerals and metals are fundamentally incredibly important to societies all over the world. The activities required to extract minerals, however, often have negative impacts on forest landscapes and habitats. Forest health is not only about deforestation; mining has been found to produce severe impacts on water and soil that can indirectly impact forest health and its ecological integrity. Moreover, impacts of mining can become significant when multiple instances of mining activities happen at the same location simultaneously, as was found in the Indonesian case studies. Therefore, there is still the need to identify and attempt to reduce the impacts of mining even in a landscape dominated by activities like agriculture and forestry. Artisanal mining is typified as formal, informal, or illegal mining operations with predominantly rudimentary technologies in the exploration and extraction by individuals or large groups of people. Small-scale mining operations can also be mechanized, or semi-mechanized, and or have a greater degree of capitalization than artisanal mining. The World Bank’s extractive industries in forest landscapes program seeks to address these challenges by promoting forest-smart extractive investments to ensure that investments in the extractives sector do not erode forest capital and instead generate positive forest outcomes. The artisanal and small-scale mining (ASM) study and the parallel study on large-scale mining (LSM) share the overarching objective of supporting the World Bank’s efforts to help client countries ensure that resource extraction from forested areas serves as a force for poverty reduction and sustainable development while respecting the environment and the needs of local communities. In order to achieve a forest-smart ASM sector, adopting an integrated approach is recommended.